Karakterisasi Gelatin Hasil Ekstraksi dari Kulit Ikan Patin (Pangasius hypophthalmus) dengan Proses Asam dan Basa - Nasution, Azlaini Yus; Harmita, Harmita; Harahap, Yahdiana (Pharmaceutical Sciences and Research, 2018)
Gelatin in the majority market comes from pigs and cows. The raw material of gelatin manufacture from other sources continue to be studied because it closely related with halal product. Currently gelatin from fish is an alternative to gelatin making. Catfish (Pangasius hypophthalmus) is a fish species developed in Kampar regency of Riau Province. The catfish skin can be used as raw material source in gelatin production. This study aims to compare the characteristics of gelatin extracted from catfish skin with acid and alkaline pretreatment. In the acid pretreatment, sulfuric acid is used until the solution at pH 3, then it is extracted with distilled water at 60ºC. In the alkaline pretreatment, the sample was added by 0.2 N NaOH followed by 0.05 N acetic acid and then extracted with distilled water at 60ºC. Characterizations done were including calculation of rendement value, organoleptic test, moisture content, pH, ash content, viscosity, gel strength and texture profile analysis using texture analyzer, protein content with Kjeldahl method and analysis amino acid with HPLC. Characterization of catfish gelatin with acid process gives the following results: rendement (14.94%), water content (9.80%), pH (5.14), ash (0.19%), viscosity (3.12 cP), protein content (97.71%), and highest amino acids, glycine = 16.90 %, proline = 11.08%, glutamic acid = 9.10 %. The result of gelatin characterizations with alkaline process: rendement (14.30%), water content (7.25%), and pH (5.35), ash content (1.54%), viscosity (5.35 cP), gel strength (141,5 g), protein content (91.92%), the highest amino acid content are glycine = 18.15%, proline = 12.30%, glutamic acid = 10.73%. Catfish gelatin through alkaline pretreatment exhibits better properties than acid pretreatment.